Transformational Leadership as a Key Factor in Improving the Performance of Healthcare Organizations - Dewi Agustina; Restu Rahayani Padang; Tia Wahyuni Dolok Saribu; Karin; Ririn Hasrat Kartika Zalukhu; Nabilla Suci Ramadhani; Silvya Rahma; Muhammad Ramadhan Ginting; Sofia Nabila; Siti Nurhamidah Harahap; Zahra Dwi Andini; Aprilyautami; Susan Limbong (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The performance of healthcare organizations is significantly influenced by the quality of leadership applied. This study aims to comprehensively examine the role of transformational leadership in improving healthcare organizational performance through a systematic literature review approach. The literature search was conducted through Google Scholar, PubMed, ScienceDirect, and ResearchGate using the keywords "transformational leadership" and "healthcare organizational performance." Of the 358 articles found, only 10 articles published between 2019 and 2024 met the inclusion criteria and were subjected to further analysis. The results of the study indicate that transformational leadership contributes significantly to increased productivity, loyalty, innovative work behavior, and employee commitment in various healthcare institutions, including hospitals, community health centers, and health offices. This leadership style has been shown to encourage the formation of a collaborative work culture and is oriented towards quality service, although its influence is not always direct because it is mediated by factors such as organizational culture, job satisfaction, and self-efficacy. These findings confirm that the implementation of transformational leadership, supported by a solid organizational system, is an effective strategy for improving performance and quality of service in the healthcare sector.